Particle shape effects in colloidal crystals and colloidal liquid crystals: Small-angle X-ray scattering studies with microradian resolution. Issue 4 (August 2015) - Petukhov, Andrei V.; Meijer, Janne-Mieke; Vroege, Gert Jan
Abstract: Small-angle X-ray scattering (SAXS) is an indispensable tool in structural investigations of self-assembled colloidal crystals and colloidal liquid crystals. This paper reviews recent studies of the particle shape effects on the crystal structure as revealed by SAXS. Rod-like, plate-like, biaxial board-like as well as cubic-like shapes are discussed. Since relatively large, (sub)micron particles are often used in these studies, we describe the principles of the microradian X-ray diffraction technique that allows detailed characterisation of the periodic order including the determination of the intrinsic width of the Bragg peaks. Graphical abstract: Highlights: The structure of colloidal crystals can be affected by the shape of the particles. Highly anisometric colloids yield a rich variety of liquid crystalline phases. Small-angle X-ray scattering is an excellent tool to unravel colloidal structures. Microradian resolution can be achieved using compound refractive optics. SAXS must be further promoted in the colloid community.